EAACI position paper: irritant‐induced asthma. Issue 9 (5th July 2014) - Vandenplas, O.; Wiszniewska, M.; Raulf, M.; de Blay, F.; Gerth van Wijk, R.; Moscato, G.; Nemery, B.; Pala, G.; Quirce, S.; Sastre, J.; Schlünssen, V.; Sigsgaard, T.; et al.
Abstract The term irritant‐induced (occupational) asthma (IIA) has been used to denote various clinical forms of asthma related to irritant exposure at work. The causal relationship between irritant exposure(s) and the development of asthma can be substantiated by the temporal association between the onset of asthma symptoms and a single or multiple high‐level exposure(s) to irritants, whereas this relationship can only be inferred from epidemiological data for workers chronically exposed to moderate levels of irritants. Accordingly, the following clinical phenotypes should be distinguished within the wide spectrum of irritant‐related asthma: (i) definite IIA, that is acute‐onset IIA characterized by the rapid onset of asthma within a few hours after a single exposure to very high levels of irritant substances; (ii) probable IIA, that is asthma that develops in workers with multiple symptomatic high‐level exposures to irritants; and (iii) possible IIA, that is asthma occurring with a delayed‐onset after chronic exposure to moderate levels of irritants. This document prepared by a panel of experts summarizes our current knowledge on the diagnostic approach, epidemiology, pathophysiology, and management of the various phenotypes of IIA.